P32 Mitochondria must choose between resistance to fatty acyl coa regulation or rapid respiration in the type 2 diabetic heart. (21st March 2018) - Kerr, Matthew; Rohling, Sara; Fialho, Maria Sousa; Lopez, Colleen; Tyler, Damian; Heather, Lisa C
Abstract : Introduction: Cardiac metabolism in type 2 diabetes is abnormal, with increased fatty-acid oxidation, and decreased glucose oxidation. We have previously shown a reduction in energetics in the type 2 diabetic heart (20% decrease in ATP). The control of respiratory rate is mediated primarily (70%) by one protein, the adenine nucleotide translocator (ANT). The ANT is inhibited by fatty acyl CoA groups which may relate the reduced energetics in the type 2 diabetic heart to its high fatty acid environment. Results: Palmitoyl-CoA (P-CoA) decreased respiration in control mitochondria by 50%, but in diabetic mitochondria by just 20%. We showed unchanged Vmax, but increased Km in the presence of P-CoA, demonstrating competitive inhibition by the fatty acyl CoA group. Diabetic mitochondria had decreased ADP stimulated, and maximal respiration compared to controls when respired on glutamate, pyruvate and malate. The addition of fatty acids rescued only the ADP stimulated respiratory defect. Finally, we showed a very strong correlation between decreased respiration, and decreased sensitivity to fatty acyl CoA regulation. Conclusion: We have shown that type 2 diabetic mitochondria are resistant to fatty acyl CoA regulation, indicating that this is unlikely to be the cause of energetic dysfunction. We have shown a strong correlation between fatty acid sensitivity and the rate of respiration, two phenomena that are intrinsically linked by the ANT. We propose that changes to ANT kinetics in type 2 diabetes provides a strong link between the high fat phenotype, and reduced energetic capacity of type 2 diabetic mitochondria.